Udział chłopów w życiu Wielunia w pierwszej połowie XVI wieku - Nowak, Tomasz Andrzej (Zeszyty Wiejskie, 2012)
The town is the place where from the outset, ways of life of different social states were crossing. New town – dwellers were coming not only from other town centers but also from nobility and peasants. Usually, in investigations on history of social nobility's composition, representatives of nobility connected with town are being observed. However, here I would like to concentrate on the problem of peasants participation in Wielun's life, to see in which context their existing in the oldest books of this town was written down. Generally, connections of peasants with town can be divided into 3 cathegories. First category was nobility who came from the village. For some time they were having contacts with their family living still in that village. The second group were people who came to town for short periods. They were forced to take care of economic or / and religious matters. The last category were peasants living in villages belonging to town.